ICT adoption and stock market development in Africa: An application of the panel ARDL bounds testing procedure - Jerry Ikechukwu Igwilo; Athenia Bongani Sibindi (Journal of Risk and Financial Management, 2021)
The nexus between Information Communication Technology (ICT) and stock market development has been predominantly based on studies of the developed markets and high-income economies of the world. The objective of this study was to examine the causal relationship between ICT adoption and stock market development in Africa. The study examined a panel of 11 African stock exchanges for the period 2008-2017 and employed the panel ARDL bounds testing procedure to test for cointegration and examine the causal relationship between ICT adoption and stock market development. The dependent variable employed was the stock market development index (FINDEX), while the independent variable was the ICT adoption index (ICTDEX), and the financial freedom index (FFI) was employed as a control variable. Firstly, the results of the study documented that the variables are cointegrated in the long term. Secondly, the results of the study documented a bi-directional causal relationship (complementarity) between ICT adoption and stock market development. In essence, ICT adoption and stock market development reinforce each other. Thirdly, the study established a causal relationship running from financial freedom to stock market development. This lends credence to the notion that financial market deregulation promotes stock market development. Lastly, a positive causal relationship that ran from financial freedom to stock market development was documented. This study contributes to the body of knowledge in the sense that it is the first study to examine the phenomenon of the ICT-stock market development nexus by employing a panel study. Hitherto, studies were mainly country-specific in nature. The findings of the research imply that policymakers should be more resolute when formulating ICT policies, as ICT adoption can drive stock market development and vice versa for better economic growth. Policymakers should embrace policies that support the deregulation of stock markets as this will lead to the development of the latter.
Keywords: G23; O16; O33; O43; 330; stock market development; economic growth; financial freedom; ICT adoption; causality; cointegration; Africa